2015
DOI: 10.1002/pssa.201532619
|View full text |Cite
|
Sign up to set email alerts
|

Source and effects of sodium in solution-processed kesterite solar cells

Abstract: Based on solution‐processed kesterite‐type Cu2ZnSn(S1–x,Sex)4 solar cells, a detailed investigation of the source and effects of sodium in the absorber will be presented. In contrast to most investigations in literature so far, the main process for sodium supply during selenization does not seem to be the diffusion out of the sodium‐containing glass substrate but a transfer from the environment into the absorber. Studies on the influence of sodium on the morphological properties of the absorbers let us assume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
2
27
0
2
Order By: Relevance
“…Since the early 1990's, it is known that Na leads to significant improvements on CIGS solar cells [33]. For kesterite solar cells, the effects of Na were thoroughly investigated [34][35][36][37] and it has been shown that Na diffusion from SLG has similar positive effects on absorber morphology and device properties in kesterite devices [37,38]. Na treatment increases grain size and improves the overall absorber layer morphology, increases doping concentration and was shown to yield improved opto-electronic properties of the absorber layer.…”
Section: Sodium (Na)mentioning
confidence: 99%
“…Since the early 1990's, it is known that Na leads to significant improvements on CIGS solar cells [33]. For kesterite solar cells, the effects of Na were thoroughly investigated [34][35][36][37] and it has been shown that Na diffusion from SLG has similar positive effects on absorber morphology and device properties in kesterite devices [37,38]. Na treatment increases grain size and improves the overall absorber layer morphology, increases doping concentration and was shown to yield improved opto-electronic properties of the absorber layer.…”
Section: Sodium (Na)mentioning
confidence: 99%
“…So far the most research attention has been paid to sodium, resulting in many thorough investigations which revealed grain size enhancement, passivation of grain boundaries, and an increase in net hole concentration as the major beneficial effects of sodium treatments. [3][4][5][6] Also lithium addition has shown to improve device performance by boosting the electronic quality of the CZTSSe absorber material and grain boundaries. [7] First studies on the effect of potassium addition confirmed advantageous effects on kesterite absorber growth and optoelectronic properties similar to Na.…”
mentioning
confidence: 99%
“…[3][4][5][6] Also lithium addition has shown to improve device performance by boosting the electronic quality of the CZTSSe absorber material and grain boundaries. [7] First studies on the effect of potassium addition confirmed advantageous effects on kesterite absorber growth and optoelectronic properties similar to Na.…”
mentioning
confidence: 99%
“…However, the Na and O concentrations correlate for all samples over all temperatures. The concentrations are increased at the air/surface and the CZTS/Mo interfaces for all samples, indicating segregation of Na and O at these interfaces . The increased SIMS intensity may also be caused by a change in sputter yield and ionization efficiency at these interfaces, making quantitative assessment challenging .…”
Section: Resultsmentioning
confidence: 98%